Weak solutions of boundary value problems in nontube domains for fourth-order equations of composite type - Korzyuk, Victor; Kovnatskaya, Olga (Mathematical Modelling and Analysis, 2011)
In the paper existence and uniqueness of weak solutions of boundary value problems in nontube domains for fourth-order equations of composite type are proved by methods of functional analysis.